Attitude and personal orientation differences between clergy of Anglican and Pentecostal denominations with particular reference to sexual ethics - Davies, Alan Bruce (Rhodes University, Faculty of Divinity, Department of Divinity, 1977)
The introduction provides a concise discussion of the confused condition of our Western sexuality. It is noted that this confusion has also manifested itself in ecclesiastical circles, and that the contribution of the church towards the resolution of 'moral' confusion in this sphere is in fact minimal. The study then proceeds to a more empirical investigation of certain phenomena which might enable us to demonstrate the close relationship which exists between the individual's psychological condition, or 'state of consciousness', and the type of theology or ethics he formulates or adopts. The present study was an investigation designed to determine whether Anglican clergy and Pentecostal pastors differed significantly with regard to theological orientation, level of self-actualization or the degree of flexibility they showed in the application of sexual values. Furthermore we were concerned to discover the inter-relation between these various traits. A third group of ordinands from St. Paul's College (C.P.S.A.) was also incorporated into the study. All forty eight subjects completed a series of tests and questionnaires which were scored according to eighteen different scales relating to selfactualzing traits, theological orientation and the application of sexual ethics. In brief the results showed that the Anglican clergy were significantly more self-actualizing, theologically liberal and more flexible in the application of sexual values than were Pentecostal pastors. Little difference was found to exist as a function of age and education, or between Anglican clergy and ordinands. Furthermore theological conservatism, general conservatism, dogmatism and inflexibility in the application of sexual ethics were all shown to correlate negatively with self-actualization. In the discussion of results the writer attempted to demonstrate the close relationship between the churchman's psychological make-up and the way in which he construes his world and formulates his theology and ethics. In the concluding discussion the writer once again widened the scope of concern in order to demonstrate how the findings of the present study can be fitted into the broader context of the life of the church. It has been suggested that the type of approach adopted by churchmen to problems of sexuality is very much determined by their psychological make up. Hence in this sense both the status of the church in modern society and the degree to which the church can assist in the resolution of our culture's problems in the field of human sexuality, is greatly dependent upon the 'states of consciousness' of our clergy.
Keywords: Clergy -- Sexual behavior; Pentecostalism -- Sexual behavior; Anglican Communion -- Clergy -- Sexual behavior; Sex -- Religious aspects -- Christianity; Christian ethics -- Anglican authors; Sexual ethics